2018
DOI: 10.1002/jcop.22091
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Brief Sense of Community Scale among youth of color from an underserved urban community

Abstract: Neighborhood sense of community (SOC) is a key construct in the community psychology literature. While the research on neighborhood SOC has progressed significantly, there is a need to further validate the Brief Sense of Community Scale (BSCS) among youth. A critical area of scholarship, therefore, is to examine the factor structure of the BSCS among a cohort of adolescents, particularly from the United States. This study tested the factor structure of the BSCS among a sample of urban youth of color (N = 383) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 52 publications
(137 reference statements)
4
41
0
Order By: Relevance
“…Membership has been defined as perceived belongingness to a community (McMillan & Chavis, ) and marking the boundary between those who are a part of community and those who are perceived to not be part of community (Mannarini et al, ). Membership also encompasses perceived sense of safety in the community and commitment (Lardier, Reid, & Garcia‐Reid, ). Influence has been defined as the perceived feeling of making a difference in the community (McMillan & Chavis, ) and community influencing the individual (Mannarini et al, ).…”
Section: Literature Review and Conceptual Framingmentioning
confidence: 99%
See 2 more Smart Citations
“…Membership has been defined as perceived belongingness to a community (McMillan & Chavis, ) and marking the boundary between those who are a part of community and those who are perceived to not be part of community (Mannarini et al, ). Membership also encompasses perceived sense of safety in the community and commitment (Lardier, Reid, & Garcia‐Reid, ). Influence has been defined as the perceived feeling of making a difference in the community (McMillan & Chavis, ) and community influencing the individual (Mannarini et al, ).…”
Section: Literature Review and Conceptual Framingmentioning
confidence: 99%
“…Needs fulfillment concerns the perception that one's needs will be met by the community or group (McMillan & Chavis, ) and resources will be shared among and between those in the community (Mannarini et al, ; Talo et al, ). Last, emotional connection has been defined as shared history through common places or experiences (McMillan & Chavis, ), and being involved in collective experiences that benefit the community at‐large (Lardier et al, ).…”
Section: Literature Review and Conceptual Framingmentioning
confidence: 99%
See 1 more Smart Citation
“…It was identified that the structural disadvantage caused by poverty reinforced the relations between neighbors, with a collective action in solving the problems (Bolland, & Debra, 2002; Walton, 2016). Thus, it is necessary to develop more research with people in situations of poverty in peripheral contexts (Flaherty, Zwick, & Bouchey, 2014; Lardier, Reid, & Garcia‐Reid, 2018; Loomis & Wright, 2018; Peterson, Speer, & Hughey, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the discussion of socio‐cultural issues is broadened. There is also the need to study the dimensions of poverty and its relations with the SC in Latin American countries with a strong social inequality (Nepomuceno, Barbosa, Ximenes, and Cardoso (2017), because most studies on the SC occur in rich countries (Flaherty et al, 2014; Lardier et al, 2018; Loomis & Wright, 2018; Peterson et al, 2006). Nepomuceno et al (2017) understand that the SC represents an important concept in the analysis of the poverty phenomenon, since it allows to gather information on how individuals and collectivities articulate themselves toward a common goal.…”
Section: Introductionmentioning
confidence: 99%